The Relationship Between Age and Gender and the Incidence of Hypertension in the Internal Ward of Massenrempulu General Hospital, Enrekang Regency - Ricky Z, Ricky Z (Journal of Asian-african Focus in Health, 2023)
Hypertension is a degenerative disease. Generally, blood pressure increases slowly with increasing age. WHO recorded that in 2012 there were at least 839 million cases of hypertension, estimated to be 1.15 billion in 2025 or around 29% of the total world population. The aim of the study was to determine the relationship between age and gender with the incidence of hypertension at Massenrempulu General Hospital, Enrekang district. The type of research used is a cross sectional design. The population in this study were all patients in the Internal Room at Massenrempulu General Hospital, Enrekang Regency in 2015, namely 272 people. The sample studied was 51 people using the nonprobability sampling method with accidental sampling technique. The research was carried out from 14 to 31 March 2016. Data was collected using a questionnaire and then statistical analysis was carried out using the chi square test with the alternative Fisher exact test with a significance level of α = 0.05. The results of the study showed that of the 51 respondents studied, based on age, the most respondents were high risk, namely 35 people (68.6%), based on gender, the most respondents were women, namely 27 people (52.9% ), and the majority of respondents experienced hypertension, namely 36 people (70.6%). Based on the research results, it was concluded that there was a relationship between age and the incidence of hypertension, with a value of p = 0.001 < 0.05, and there was a relationship between gender and the incidence of hypertension, with a value of p = 0.002 < 0.05. It is recommended that health service officers always strive to provide information to the public by providing health education in an effort to develop strategies to prevent, reduce or control morbidity rates among hypertension sufferers in their work areas.